Myeloid-derived suppressor cells and their subsets serve as potential biomarkers for the progression of brucellosis - Shi, Juan; Maimaiti, Yibeibaihan; Qi, Xinxin; Chen, Na; Shi, Huidong; Ding, Jianbing; Zhu, Yuejie; Zhang, Fengbo (Frontiers in Microbiology, 2026)
BackgroundBrucellosis remains the most prevalent zoonotic disease globally and can cause chronic persistent infection, which in turn results in prolonged recovery challenges. Myeloid-derived suppressor cells (MDSCs) are pathologically activated neutrophils and monocytes with strong immunosuppressive activity. Toll-like receptor 4 (TLR4) can initiate the body’s inflammatory response, leading to an inflammatory cytokine storm. Programmed death ligand 1 (PD-L1) modulates the strength and duration of the immune response, diminishing the immune system’s ability to eliminate pathogens and subsequently affecting disease progression and prognosis. However, the clinical significance of TLR4+MDSC and PD-L1+MDSC in Brucella infection remains unclear.MethodsA total of 88 patients with acute brucellosis infection (ABI), 66 patients with chronic brucellosis infection (CBI), and 82 healthy controls (HC) subjects were enrolled. Flow cytometry was used to detect TLR4+MDSCs and PD-L1+MDSCs of patients. ELISA was used to detect ALT, AST, Arg1 and iNOS in the patient’s serum. We characterized a mouse model of Brucella, and determined the effects of TLR4+MDSCs and PD-L1+MDSCs in this model.ResultsOur study found that the frequency of MDSC in CBI group was significantly elevated. The levels of Arg1 and iNOS were also positively correlated with the levels of TLR4+MDSCs and PD-L1+MDSCs. The levels of AST and ALT had elevated may reflect liver function. In addition, we also found that the number of TLR4+MDSCs and PD-L1+MDSCs increased in model mice with chronic brucellosis.ConclusionThese findings expand the current understanding of persistent Brucella infection, and highlight that TLR4+ and PD-L1+ MDSCs hold potential as candidate biomarkers for assessing the severity and progression of brucellosis.